Pemanfaatan Nira sebagai Starter Alami dalam Pembuatan Bolu Pandan (Pandanus amaryllifolius) sebagai Pengganti Ragi Komersial - Wan Siti Humaira Kenanga; Rabithah Hanny Sembiring; Fathur Rahman; Riski Amelia Nasution (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The use of natural leavening agents in food products has emerged as an alternative to reduce dependence on commercial yeast. This study aimed to evaluate the potential of palm sap as a natural starter in the production of pandan sponge cake (Pandanus amaryllifolius) and to compare its physical, microbiological, chemical, and sensory characteristics with those produced using commercial yeast. An experimental method employing a Completely Randomized Design (CRD) with two treatments was applied: P1 (natural palm sap starter) and P2 (commercial yeast). The observed parameters included dough expansion, pH value, yeast and mold count, and sensory evaluation covering color, aroma, texture, and taste. Data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level. The results demonstrated that the natural palm sap starter produced a faster fermentation response than commercial yeast, exhibited a lower yeast and mold count of 2.70 × 10² CFU/g within food safety standards, and achieved higher panelist preference scores across all sensory attributes. Although it produced a slightly denser texture, palm sap has strong potential as a safe, environmentally friendly natural leavening agent capable of producing pandan sponge cake with desirable sensory quality.